Thermodynamically consistent phase-field modeling for polycrystalline multi-phase continua - Westermann, Hendrik; Mahnken, Rolf (International Journal of Solids and Structures)

Basisdimensionen der Unterrichtsqualität im Kontext des Erwerbs digitaler Kompetenzen an resilienten Schulen - Drossel, Kerstin; Niemann, Jan; Oldak, Anna; Eickelmann, Birgit (Zeitschrift für Bildungsforschung)
Zusammenfassung Die fortschreitende Digitalisierung stellt Schulen vor Herausforderungen, insbesondere bei der Nutzung digitaler Medien in unterrichtlichen Lehr- und Lernprozessen mit dem Ziel, den (über-) fachlichen Kompetenzerwerb aller Schüler*innen zu unterstützen. Betrachtet man die digitalen Kompetenzen, zeigt sich, dass auch diese sozialen Disparitäten unterliegen. Dennoch lassen sich in ICILS organisational resiliente Schulen identifizieren, deren Schüler*innen trotz herausfordernder Schüler*innenkomposition überdurchschnittliche digitale Kompetenzen erreichen. Studien, die fachspezifische Kompetenzen untersuchen, lassen erkennen, dass organisational resiliente Schulen gemeinsame Merkmale aufweisen. Ein Merkmal, das in diesem Zusammenhang bedeutsam erscheint, ist die Gestaltung von Unterrichtsqualitätsmerkmalen. Digitale Kompetenzen erscheinen diesbezüglich unerforscht, sodass der vorliegende Beitrag mittels Daten aus der BMBF-geförderten qualitativen ICILS-Vertiefungsstudie UneS-ICILS 2018 (Unerwartbar erfolgreiche Schulen im digitalen Wandel) Basisdimensionen von Unterrichtsqualität an resilienten Schulen in Bezug auf digitale Kompetenzen untersucht. Für die Analyse wurden 22 leitfadengestützte Interviews mit Lehrkräften und sieben Gruppeninterviews mit Schüler*innen im Hinblick auf eine ‚effiziente Klassenführung‘, ‚kognitive Aktivierung‘ und ‚konstruktive Unterstützung‘ inhaltsanalytisch ausgewertet. Im Ergebnis zeigt die Analyse der Dimension ‚effiziente Klassenführung‘, dass sich u. a. die Organisation und Struktur mittels digitaler Medien wie beispielsweise durch den Einsatz digitaler Lernplattformen als bedeutende Faktoren herausstellen. Hinsichtlich der ‚kognitiven Aktivierung‘ wird der Einsatz digitaler Tools für das Anknüpfen an individuelles Vorwissen als bedeutend hervorgehoben. Darüber hinaus zeigt sich bei der Dimension ‚konstruktive Unterstützung‘ die Förderung des selbstgesteuerten Lernens und das Ausbilden von Unterstützungsstrukturen zum (kooperativen) Lernen mit digitalen Medien als bedeutsam. Induktiv ergänzt wurde die Dimension ‚Inhaltswahl und selektive Fokussierung‘, die die hohe Relevanz des Erwerbs digitaler Kompetenzen im Unterricht an den resilienten Schulen verdeutlicht.

Chances of smart Views: Integration of Stakeholder perspectives using videobased Views in MBSE - Förster, Felix; Bausen, Steffen; Bernijazov, Ruslan; Koldewey, Christian; Dumitrescu, Roman; Bursac, Nikola (Stuttgarter Symposium für Produktentwicklung SSP 2025)

DNA Origami Adsorption and Lattice Formation on Different SiOx Surfaces - Pothineni, Bhanu Kiran; Theile-Rasche, Chantal; Müller, Hendrik; Grundmeier, Guido; de los Arcos de Pedro, Maria Teresa; Keller, Adrian (Chemistry – A European Journal)
Self-assembled DNA origami lattices on silicon oxide surfaces have great potential to serve as masks in molecular lithography. However, silicon oxide surfaces come in many different forms and the type and history of the silicon oxide has a large effect on its physicochemical surface properties. Therefore, we here investigate DNA origami lattice formation on differently fabricated SiOx films on silicon wafers after wet-chemical oxidation by RCA1. Despite having similar oxide compositions and hydroxylation states, of all surfaces tested, only thermally grown SiOx performs similarly well as native oxide. For the other SiOx films deposited by plasma-enhanced chemical vapor deposition and magnetron sputtering, DNA origami adsorption is strongly suppressed. This is attributed to an increased surface roughness and a lower oxide density, respectively. Our results demonstrate that the employed SiOx surface may decide over the outcome of an experiment and should be considered as an additional parameter that may require optimization and fine-tuning before high-quality lattices can be assembled. In particular, our observations suggest that efficient DNA origami lattice assembly on SiOx surfaces requires a low surface roughness and a high oxide density.

DNA origami nanostructures in biomedicine and the issue of stability - Keller, Adrian (Nucleic Acid Insights)

"Irgendwann kommt ein Kind / Es wird geboren in Wien, Wien, Wien, Wien". Stadt- und Selbstmythisierung als künstlerische Strategie bei RAF Camora - Spener, Anna Maria (Deutschrap als Lyrik der Gegenwart. Literaturwissenschaftliche Perspektiven)

Toward a multilayered framework of privacy-related decision-making in B2B - Schumann, Jan H.; Zimmermann, Johanna; Steinhoff, Lena; Totzek, Dirk; van der Borgh, Michel; Martin, Kelly D. (Journal of Business Research)
For business-to-business (B2B) supplier firms that increasingly infuse technology into their offerings such that they can provide data-driven services, ready access to proprietary B2B customer firm data is critical. Despite clear evidence that B2B customer firms hesitate to provide such data due to the associated privacy risks, limited evidence exists regarding how B2B customer firms engage in privacy-related decision-making. Such knowledge is crucial to efforts to address privacy-related challenges by designing and managing B2B services effectively. Therefore, informed by a systematic analysis of the current state of research on privacy-related decision-making in B2B contexts, this article derives a comprehensive research framework from B2B buying research. The framework conceptualizes privacy-related decision-making in B2B as a multilayered phenomenon and indicates key questions for continued research on pressing managerial challenges for B2B services and solutions providers.

Telling Oneself through Someone Else’s Life: Jeannette Walls’s Half Broke Horses - Mildorf, Jarmila (Partial Answers)

Dynamische Preisgestaltungsstrategien und ihre Auswirkungen im E-Commerce - Heyden, Lucas; Husemann-Kopetzky, Markus; Brock, Christian; Steinhoff, Lena (Digital Analytics im Dienstleistungsmanagement – Customer Insights, Prozesse der Künstlichen Intelligenz, Digitale Geschäftsmodelle)

Performing Selves in the 21st Century: Introduction - Fonioková, Zuzana; Mildorf, Jarmila (Partial Answers)

Performing Selves in the 21st Century (Partial Answers)

Associations of carbohydrate quality and cardiovascular risk factors vary among diabetes subtypes. - Weber, KS; Schlesinger, S; Goletzke, J; Straßburger, K; Zaharia, OP; Trenkamp, S; Wagner, R; Lieb, W; Buyken, Anette; Roden, M; Herder, C; group, GDS (Cardiovasc Diabetol)

Effect of a controlled lifestyle intervention on medication use and costs: The Healthy Lifestyle Community Program (cohort 2). - Kranz, RM; Kettler, C; Anand, C; Koeder, C; Husain, S; Schoch, N; Buyken, Anette; Englert, H (Nutr Health)

Abschreibungen als Mittel der Investitionsförderung in Deutschland – Möglichkeiten, Grenzen und Perspektiven evidenzbasierter Analysen - Dyck, Daniel; Hechtner, Frank; Maiterth, Ralf; Sureth-Sloane, Caren

L’islam dans la culture populaire: Reconfigurations et nouvelles visiblités - Karaca, Resul (Introduction)

Responsible Loyalty Programs: How Redemptions for a Cause Impact Customer Loyalty - Alberternst, Benedikt; Steinhoff, Lena; Woisetschläger, David M (2025 AMA Winter Academic Conference Proceedings)

Unlocking Spiritual Value: Magical Experiences of Commercial Services - Witte, Carina; Steinhoff, Lena (2025 AMA Winter Academic Conference Proceedings)

Unintended Consequences of Selling B2B Digital Subscription Add-Ons for Customer Onboarding - Steinhoff, Lena; Kim, Jisu J.; Kanuri, Vamsi K.; Palmatier, Robert W. (Journal of the Academy of Marketing Science)
Business-to-business (B2B) software-as-a-service (SaaS) providers increasingly bundle add-on services with their core service. The implications of such bundles for onboarding customers to the relationship remain unclear; in particular, the common practice of trying to maximize add-on bundling during the customer acquisition phase arguably might conflict with goals to achieve long-term retention of customers. The current study therefore focuses explicitly on the impact of add-on bundling on customer retention during the onboarding stage, using multiple methods. A theories-in-use exploration suggests that the positive effects of add-on bundling may not manifest in the initial relational stage of customer onboarding. A field study involving a B2B SaaS provider further reveals that bundling more add-on services can significantly decrease customer retention during the onboarding stage. Moving to leaner communication channels can aggravate such attrition. Finally, a cross-industry survey of B2B managers identifies complexity perceptions as the likely source of these detrimental effects of add-on bundling during the customer onboarding stage.

Qualifikationen für Bewegung, Spiel und Sport im Ganztag an Grundschulen. Einblicke in Schulen in Nordrhein-Westfalen und Niedersachsen - Noetzel, Ida; Fögen, Yvonne; Satzinger, Nicole; Kehne, Miriam (sportunterricht)

Stochastic Euler-Poincaré reduction for central extension - Suri, Ali (Differential Geometry and its Applications)